Learning English Through Out‐of‐School Exposure: How Do Word‐Related Variables and Proficiency Influence Receptive Vocabulary Learning?. Issue 2 (6th November 2019) - De Wilde, Vanessa; Brysbaert, Marc; Eyckmans, June
Abstract : This study aimed to investigate which word‐related variables play a role in Dutch‐speaking children's L2 word learning through out‐of‐school exposure prior to classroom instruction in the foreign language. We used different measures to investigate the role of frequency, concreteness, cognateness, and age of acquisition (AoA) in receptive vocabulary learning. The results showed that cognateness and L1 AoA were important predictors of receptive word knowledge for all the participants. The findings confirmed that cognateness is important in vocabulary learning and that less proficient learners tend to guess the meaning of words based on their L1. The results also showed significant interactions between proficiency and cognateness, frequency, AoA, and concreteness, indicating that more proficient L2 learners are open to L2‐related variables such as L2 word frequency. This indicates that word‐related variables contribute in different ways according to learners' proficiency levels. Open Practices: This article has been awarded the Open Data badge. All data are publicly accessible through the Open Science Framework at https://osf.io/ndr47/ and via the IRIS database at https://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :